Fabrication and Evaluation of Atmospheric Corrosion Monitoring (ACM) Sensor of Fe-Cu Galvanic Couple - Pradhan, Rabina Nuchhe; Yadav, Brahamdeo; Lama, Prakash Chandra; Shrestha, Suman; Neupane, Shova; Gupta, Dipak Kumar; Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2017)
available with ulltext.